H19X‐encoded miR‐322(424)/miR‐503 regulates muscle mass by targeting translation initiation factors. Issue 6 (26th October 2021) - Liang, Rui; Shen, Xiaopeng; Wang, Fan; Wang, Xin; DesJarlais, Alex; Syed, Anam; Saba, Raymond; Tan, Zhi; Yu, Fang; Ji, Xuan; Shrestha, Shreesti; Ren, Yinghong; et al.
Abstract: Background: Skeletal muscle atrophy is a debilitating complication of many chronic diseases, disuse conditions, and ageing. Genome‐wide gene expression analyses have identified that elevated levels of microRNAs encoded by the H19X locus are among the most significant changes in skeletal muscles in a wide scope of human cachectic conditions. We have previously reported that the H19X locus is important for the establishment of striated muscle fate during embryogenesis. However, the role of H19X‐encoded microRNAs in regulating skeletal mass in adults is unknown. Methods: We have created a transgenic mouse strain in which ectopic expression of miR‐322/miR‐503 is driven by the skeletal muscle‐specific muscle creatine kinase promoter. We also used an H19X mutant mouse strain in which transcription from the locus is interrupted by a gene trap. Animal phenotypes were analysed by standard histological methods. Underlying mechanisms were explored by using transcriptome profiling and validated in the two animal models and cultured myotubes. Results: Our results demonstrate that the levels of H19X microRNAs are inversely related to postnatal skeletal muscle growth. Targeted overexpression of miR‐322/miR‐503 impeded skeletal muscle growth. The weight of gastrocnemius muscles of transgenic mice was only 54.5% of the counterparts of wild‐type littermates. By contrast, interruption of transcription from the H19X locus stimulates postnatal muscle growth by 14.4–14.9% and attenuates the loss of skeletal muscle mass in response to starvation by 12.8–21.0%. Impeded muscle growth was not caused by impaired IGF1/AKT/mTOR signalling or a hyperactive ubiquitin–proteasome system, instead accompanied by markedly dropped abundance of translation initiation factors in transgenic mice. miR‐322/miR‐503 directly targets eIF4E, eIF4G1, eIF4B, eIF2B5, and eIF3M. Conclusions: Our study illustrates a novel pathway wherein H19X microRNAs regulate skeletal muscle growth and atrophy through regulating the abundance of translation initiation factors, thereby protein synthesis. The study highlights how translation initiation factors lie at the crux of multiple signalling pathways that control skeletal muscle mass.